Fabrication of a magnesium alloy with excellent ductility for biodegradable clips. (1st January 2016) - Ikeo, Naoko; Nakamura, Ryota; Naka, Kosuke; Hashimoto, Toshiaki; Yoshida, Toshihiko; Urade, Takeshi; Fukushima, Kenji; Yabuuchi, Hikaru; Fukumoto, Takumi; Ku, Yonson; Mukai, Toshiji
Graphical abstract: Abstract: To develop a biodegradable clip, the equivalent plastic strain distribution during occlusion was evaluated by the finite element analysis (FEA) using the material data of pure Mg. Since the FEA suggested that a maximum plastic strain of 0.40 is required to allow the Mg clips, the alloying of magnesium with essential elements and the control of microstructure by hot extrusion and annealing were conducted. Mechanical characterization revealed that the Mg–Zn–Ca alloy obtained by double extrusion followed by annealing at 673 K for 2 h possessed a fracture strain over 0.40. The biocompatibility of the alloy was confirmed here by investigating its degradation behavior and the response of extraperitoneal tissue around the Mg–Zn–Ca alloy. Small gas cavity due to degradation was observed following implantation of the developed Mg–Zn–Ca clip by in vivo micro-CT. Histological analysis, minimal observed inflammation, and an only small decrease in the volume of the implanted Mg–Zn–Ca clip confirmed its excellent biocompatibility. FEA using the material data for ductile Mg–Zn–Ca also showed that the clip could occlude the simulated vessel without fracture. In addition, the Mg–Zn–Ca alloy clip successfully occluded the renal vein. Microstructural observations using electron backscattering diffraction confirmed that dynamic recovery occurred during the later stage of plastic deformation of the ductile Mg–Zn–Ca alloy. These results suggest that the developed Mg–Zn–Ca alloy is a suitable material for biodegradable clips. Statement of significance: Since conventional magnesium alloys have not exhibited significant ductility for applying the occlusion of vessels, the alloying of magnesium with essential elements and the control of microstructure by hot extrusion and annealing were conducted. Mechanical characterization revealed that the Mg–Zn–Ca alloy obtained by double extrusion followed by annealing at 673 K for 2 h possessed a fracture strain over 0.40. The biocompatibility of the alloy was confirmed by investigating its degradation behavior and the response of extraperitoneal tissue around the Mg–Zn–Ca alloy. Finite element analysis using the material data for the ductile Mg–Zn–Ca alloy also showed that the clip could occlude the simulated vessel without fracture. In addition, the Mg–Zn–Ca alloy clip successfully occluded the renal vein. Microstructural observations using electron backscattering diffraction confirmed that dynamic recovery occurred during the later stage of plastic deformation of the ductile Mg–Zn–Ca alloy.